Magnitude, structure and dynamics of chronic unemployment in Denmark, Finland and Germany - Simo Aho; Regina Konle-Seidl; Iben Nørup; Thomas Rhein; Thomas Rothe (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2019)
Individual unemployment spells are frequently interrupted by short casual employment, by participation in active labour market policy (ALMP) measures or by periods outside the labour force. Such episodes end unemployment spells but afterwards the person gets often unemployed again, and the conventional statistics do not capture the actual length of the individual problem of being without a "real" job in the longer run. To better grasp this problem of repeated unemployment we analyse unemployment trajectories of individuals with weak links to the labor market in the longer run. For this purpose, we introduce the concept of "chronic unemployment" (CU). Our empirical analysis applies unique comparable and very detailed longitudinal register data to study the CU problem in Denmark, Finland and Germany. We find that chronically unemployed make up about one third of all unemployed in all three countries. This means that a substantial part of the unemployed has not gained a stable foothold in the open labour market for a long time. Individual factors strongly influence the probability of being chronically unemployed. CU becomes more common with age and decreases as the level of education increases. Although persistence in CU is highest in Germany, the country realizes higher transition rates into stable employment than the Nordic countries. Active labour market policy measures have a positive impact on the transition from chronic unemployment to non-subsidized employment, particularly wage subsidies in the private sector and occupational training and qualification. – – Phasen der Arbeitslosigkeit werden häufig durch kurze Zeiten der Beschäftigung, durch die Teilnahme an arbeitsmarktpolitischen (ALMP) Maßnahmen oder durch einen zeitweisen Rückzug vom Arbeitsmarkt unterbrochen. Solche Episoden beenden die Arbeitslosigkeitsdauer, aber danach wird die Person oft wieder arbeitslos. Das Problem, langfristig ohne "echten" Job zu sein, wird aber von herkömmlichen Statistiken nicht angemessen erfasst. Mit unserem Konzept der "chronischen Arbeitslosigkeit" können wir dieses Problem besser analysieren. Auf der Basis von vergleichbaren und sehr detaillierten amtlichen Längsschnittdaten untersuchen wir das Phänomen in Dänemark, Finnland und Deutschland. In allen drei Ländern machen chronisch Arbeitslose etwa ein Drittel aller Arbeitslosen aus. Individuelle Charakteristika haben einen großen Einfluss auf die Wahrscheinlichkeit, chronisch arbeitslos zu sein. In Deutschland verbleiben chronisch Arbeitslose am längsten in diesem Zustand. Trotzdem sind die Übergangsraten in eine stabile Beschäftigung in Deutschland höher als in den zwei nordischen Ländern. Aktive arbeitsmarktpolitische Maßnahmen wirken sich positiv auf den Übergang von der chronischen Arbeitslosigkeit in nicht subventionierte, nachhaltige Beschäftigung aus. Am effektivsten sind Eingliederungszuschüsse sowie berufliche Bildungs- und Qualifizierungsmaßnahmen.
Keywords: C81; E24; J21; J69; 330; Administrative data; long-term unemployment; recurrent unemployment; active labour market policy